„Wie eine schnelle Eingreiftruppe“. Russische Prokriegslyrik über den Krieg gegen die Ukraine (2022–2024) - Schmidt, Henrike (Wiener Slawistischer Almanach, 2025)
Russian poetry is not only written against, but also for the war that Russia has been waging in and against Ukraine since 2014 and 2022. The article maps the field of this pro-war poetry, which includes different segments of ‘professional’, i.e. literary institutionalised, and autodidactic, graphomaniacal poetry that often emerges spontaneously in social networks. It examines the institutional and media framing of this propaganda poetry as part of a hybrid media environment characterised by the interplay of social media, television and book publishing. Particular attention is paid to the aspect of anthologising such war poetry. The article proposes the hypothesis that the massive, timely anthologisation of contemporary war poetry is intended not only to achieve goals of mobilisation and propaganda, but also to shape future historical narratives, the ‘latest national epic’.